Occupational and non-occupational attributable risk of asbestos exposure for malignant pleural mesothelioma. Issue 6 (7th February 2014) - Lacourt, A; Gramond, C; Rolland, P; Ducamp, S; Audignon, S; Astoul, P; Chamming's, S; Gilg Soit Ilg, A; Rinaldo, M; Raherison, C; Galateau-Salle, F; Imbernon, E; et al.
Abstract : Objectives: To estimate the proportion of pleural mesothelioma cases that can be attributed to asbestos exposure in France including non-occupational exposure. Methods: A population-based case-control study including 437 incident cases and 874 controls was conducted from 1998 to 2002. Occupational and non-occupational asbestos exposure was assessed retrospectively by two expert hygienists. ORs of pleural mesothelioma for asbestos-exposed subjects compared to non-exposed subjects, and population-attributable risk (ARp) of asbestos exposure were estimated using a conditional logistic regression. Results: A clear dose-response relationship was observed between occupational asbestos exposure and pleural mesothelioma (OR=4.0 (99% CI 1.9 to 8.3) for men exposed at less than 0.1 f/mL-year vs 67.0 (99% CI 25.6 to 175.1) for men exposed at more than 10 f/mL-year). The occupational asbestos ARp was 83.1% (99% CI 74.5% to 91.7%) for men and 41.7% (99% CI 25.3% to 58.0%) for women. A higher risk of pleural mesothelioma was observed in subjects non-occupationally exposed to asbestos compared to those never exposed. The non-occupational asbestos ARp for these subjects was 20.0% (99% CI −33.5% to 73.5%) in men and 38.7% (99% CI 8.4% to 69.0%) in women. When considering all kinds of asbestos exposure, ARp was 87.3% (99% CI 78.9% to 95.7%) for men and 64.8% (99% CI 45.4% to 84.3%) for women. Conclusions: Our study suggests that the overall ARp in women is largely driven by non-occupational asbestos exposure arguing for the strong impact of such exposure in pleural mesothelioma occurrence. Considering the difficulty in assessing domestic or environmental asbestos exposure, this could explain the observed difference in ARp between men and women.